Pengaruh Kepuasan Kerja Guru dan Kepuasan yang Diperoleh Siswa Terhadap Profitabilitas - Chendranatha, Yonathan (Business Accounting Review, 2013)
The growth and competition in the educational service is extremely tight, especially in the high school level ini wich each school compete in doing a wide range of strategies to be able to attract students to the maximum. With the growing number of new students who are interested to enter high schools then the financial sustainability will be maintained so that the improvement of the quality and performance of the school can be optimized. One of the things that became an important role in improving the performance and quality of a high school was the performance of the high school teachers to see the explanation above and to see how important the job satisfaction of teachers towards financial sustainability and performance of a high school, it will be examined the influence of job satisfaction of teachers toward financial sustainability in senior high school by using the concept of Balance Scorecard